Intervensi Mindfulness terhadap Caring Perawat - Listiowati, Sri; Dwidiyanti, Meidiana; Dwiantoro, Luky (Journal of Telenursing (JOTING), 2023)
The study aims to analyze and determine whether mindfulness interventions can increase nurses' care level towards patients. The method used is the literature review method. The research results show that mindfulness intervention can significantly benefit nurses in improving care services' caring abilities. Mindfulness interventions can help nurses become more aware of themselves and their emotions when caring for patients. Regular mindfulness practice can reduce the level of stress and fatigue experienced by nurses at work so that they can avoid emotional exhaustion, which has the potential to interfere with interactions with patients, and become more aware and focused on the current situation. Nurses can provide complete attention to patient needs, help reduce errors caused by inattention, and improve the overall quality of care. In conclusion, mindfulness interventions can increase nurses' empathy towards patients in a caring environment that often demands high levels of heart. Nurses who practice mindfulness tend to understand better and feel patients' feelings and needs. In conclusion, mindfulness intervention can be a solution to improve nurses' caring. Keywords: Mindfulness, Caring, Nurse